Determination of some Optimal Conditions for Analyzing the two Organophosphorus Pesticides Dimethoate and Dichlorovos in Greenhouses' Soil in Burj–Islam - Lattakia by HPLC (Latakia University Journal -Basic Sciences Series, 2020)
This study was conducted in Lattakia Governorate (Burj Islam Village) to study the level of contamination of the greenhouses soil with the two organic phosphorous pesticides Dimethoate and Dichlorovos. The optimal wavelength was determined for the analysis of both pesticides using High Performance Liquid Chromatography (HPLC) technology with UV/DAD detector. According to the results, the optimal wavelength for the analysis of Dimethoate is 200 nm, while it was 195 nm for the analysis of Dichlorovos. The recovery of Dimethoate was estimated at wavelength 200 nm which was 101.33 ± 3.868 and for dichlorvos at wavelength 195 nm when it was 98.995 ± 2.078. The results also showed that the greenhouses soil were contaminated with the residues of both pesticides, Dimethoate was detected in concentrations between (0.839 - 2.668) ppm, while Dichlorovos concentrations were between (10.046 - 44.359) ppm, indicating extensive use of both especially Dichlorovos, whose concentrations were higher than Dimethoate's in the studied sites.